Right ventricular failure in congenital heart disease - Friedberg, Mark K (Curr Opin Pediatr, 2019)
PURPOSE OF REVIEW: We aim to review select literature pertaining to congenital heart disease (CHD)-induced right ventricular (RV) function and failure. RECENT FINDINGS: We review recent findings pertaining to children and adults with repaired tetralogy of Fallot (rTOF), systemic RV and hypoplastic left heart syndrome (HLHS). We emphasize pathophysiological mechanisms contributing to RV dysfunction in these conditions, the risk factors for adverse outcomes and the continuing challenges in treating these patients. We discuss how recent pathology findings, as well as developments in imaging and computer modeling have broadened our understanding of the pathophysiology of these conditions. We further review developments in the molecular and cellular basis of RV failure; and in particular, the RV molecular response to stress in repaired tetralogy of Fallot (rTOF). We highlight some of the genetic complexities in HLHS and how these may influence the long-term outcomes in these patients. SUMMARY: Recent literature has led to new understandings in the pathology, pathophysiology, risk factors for adverse outcomes, molecular and genetic basis for RV dysfunction and failure in CHD. Although these findings provide new therapeutic targets, the treatment of RV failure at this time remains limited.